Demystifying the Role of Stakeholder Pressure and Competitive Advantage on Environmental Performance of Readymade Garments Industries in Bangladesh - Chowdhury, Mohammed Ali Arshad; Dey, Mouri; Rahman, Mohammad Morshedur; Ali, Mostafa (Journal of Environmental Accounting and Management, 2026)
In terms of growth and economic development, ready-made garments (RMG) are playing a significant role through income generation, employment, standard of living and women empowerment in Bangladesh. The government and the policy makers have taken initiatives to move ahead to the development path so that the environmentally vulnerable country can prepare itself to attain sustained development goals. Environmental sustainability is the managerial philosophy of today's business world that stresses on performance, growth, survival and response to changing environment. The impact of climate change calls for taking the responsibility by the businesses so that we can keep the world livable for the future generations. Environment and business complement each other in several ways. Being pressurized by some strategic factors, garments industries in Bangladesh are adopting sustainability programs for its long-term survival. This study attempted to find out the factors responsible for the environmental performance. It employed a survey questionnaire to know the motivational factors of environmental performance. This study adopted OLS method for data analysis. Based on 156 data sets, the study confirmed that regulations, competitive advantage and stakeholders' pressure play significant role of stimulators of environmental performance. The resource persons, think tank and policy makers should make sure of formulation and proper implementation of legal issues and compliance. Incorporation of stakeholders' insight and expectations and gaining inimitable competitive advantage over a sustained time period should also be a managerial concern.